EVALUASI PEMECAH GELOMBANG (BREAKWATER) PADA PELABUHAN PERIKANAN - Agung, Lucky Wahana (Universitas Muhammadiyah Jember, 2017)
In the existing condition of the breakwater at the fishery port of IPP Pancer there is a lack of efficiency to withstand the waves, because the breakwater condition has decreased the elevation caused by very large wave power, that is because the position of the port in IPP Pancer is the dominant southern sea with very large waves . So it will disrupt the placement of ships on the dock and also passing fishermen when loading and unloading fish because the elevation of the breakwater is too low. In order to protect the coastal fishery port of Banyuwangi District, the re-planning of breakwater construction is intended to evaluate the existing condition described above, in order to obtain an efficient breakwater construction planning result. In this breakwater planning evaluation, we get the type and type of breakwater on the sloping side with armor tetrapod with 1: 2 slope. For dimensions and breakwater elevation, it is known that the length of STA 0 - 780 m, 6.8 m breakwater elevation, 1.6 m wide end portion and 1.5 m of arm. Then for the tetrapod armor with 4.3 m3 of the tip and 3.4 m3 of the arm. Sehinggga of the evaluation is able to withstand the onslaught of waves, because of the calculation of breakwater stability is able to achieve a safe value of 1.8 Msf or 1.8 1 Msf.Keywords:Breakwater Planning